One-step synthesis of nitrogen, sulfur co-doped carbon nanodots and application for Fe3+ detection. Issue 21 (18th May 2018) - Qie, Xingwang; Zan, Minghui; Miao, Peng; Li, Li; Chang, Zhimin; Ge, Mingfeng; Gui, Ping; Tang, Yuguo; Dong, Wen-Fei
Abstract : Carbon nanodots (CDs) are novel forms of zero-dimensional carbonaceous nanomaterials, which have attracted the attention of researchers. Abstract : Carbon nanodots (CDs) are novel forms of zero-dimensional carbonaceous nanomaterials, which have attracted the attention of researchers. Long wavelength emission decreases the interference of auto-fluorescence of tissue and can also penetrate more deeply. However, it is still a challenge to develop red emissive CDs. In this work, nitrogen, sulfur co-doped CDs are synthesized with red light emission through one-step solvothermal treatment. The as-synthesized CDs exhibit excellent properties such as high chemical stability, good biocompatibility, excellent photoluminescence properties, good water solubility, and low toxicity, and also show high sensitivity and selectivity towards Fe 3+ sensing. The detection limit is as low as 17.3 nM. In addition, the CDs are successfully utilized for monitoring Fe 3+ in living cells, which demonstrates their promising applicability in bioimaging. Furthermore, a test paper based on the CQDs has been prepared. This developed nanosensor can detect Fe 3+ visually and sensitively without any further steps which will make a great contribution to the development of ion sensors.